Surgical Emergencies in the Cancer Patient - Fong, Yuman; Kauffmann, Rondi Marie; Marcinkowski, Emily; Singh, Gagandeep; Schoellhammer, Hans F.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This text provides a comprehensive textbook summarizing the presentation, workup, and surgical solutions for common emergencies in the cancer patient. The use of medications (antibiotics, hormones, and biologic therapies) and interventional radiologic procedures as adjuncts or as replacements for the surgical solutions are discussed. The text covers emergencies that result as adverse effects for the systemic and local treatments for cancer, emergencies that result from mechanical issues with the cancer and those that result from surviving major extirpative surgery. Diagnosis and treatment of patients' immune-compromised or thrombocytopenic status from chemotherapy is discussed, as is surgical treatment in patients with prior complex surgical therapy or radiation treatment. Finally, the text covers alternatives to surgery, including new interventional radiologic and endoscopic procedures. Surgical Emergencies in the Cancer Patient will be of great value to healthcare professionals at all levels who are involved in the treatment of emergencies in the cancer patient. It is meant for a wide group of individuals, including medical students, residents in surgery and internal medicine, fellows in surgery and oncology, and practicing oncologists and surgeons. This work is meant to be a textbook for the student, a guide for the practitioner, and a reference for the general oncologist.
Preoperative Evaluation of the Cancer Patient for Emergency Surgery -- Toxicity of Anti-Neoplastic Therapy and Considerations for Peri-operative Care -- Surgical Considerations and Emergencies in the Cancer Patient Receiving Immunotherapy -- Surgery in the Thrombocytopenic and Coagulopathic Patient -- Emergency Surgery after Previous Radiation Therapy -- Emergent Image Guided Treatments in the Cancer Patient -- Cross-sectional and Nuclear Imaging as part of Emergency Workup -- Thoracic Emergencies: Tracheobronchial, Pulmonary, and Pleural Diseases -- Esophageal and Mediastinal Emergencies in the Cancer Patient -- Diagnostic Approach to Life-threatening Pulmonary Infiltrates -- Colon and Rectal Surgical Emergencies -- Hepatobiliary Emergencies -- Pancreatic Emergencies in the Cancer Patient -- Endocrine Surgical Emergencies in the Cancer Patient -- Surgical Emergencies in Gynecologic Oncology -- Fulminating Soft Tissue Infections -- Neurological Emergencies -- Vascular Emergencies in Oncologic Surgery -- Surgical Management of Head & Neck Emergencies in the Cancer Patient -- Surgical Emergencies in Breast Surgery -- Pediatric Perioperative Complications and Emergencies -- Dermatologic Emergencies -- Management of Catheter-related Blood Stream Infections in Cancer Patients -- Management of Perioperative Medications including Steroids, Growth Factors, and Hormone Receptors -- Emergencies in Patients with Bone-marrow Transplant -- Emergencies after Solid Organ Transplant: Liver Transplantation -- Surgery for Cancer after Previous Bariatric Surgery -- Emergencies after Cytoreductive Surgery and Hyperthermic Intraperitoneal Chemotherapy (HIPEC) -- Hepatic Artery Infusion (HAI) for Colorectal Liver Metastases and Complications of HAI Pump.-.
Keywords: Medicine; Oncology; Surgery; Surgical oncology; Medicine & Public Health; General Surgery; Surgical oncology; Oncology